Study of prescription practice for Antipsychotic drugs by Psychiatrists- A Survey - Ratnaparakhi, Mukesh; Mohanta, Guru Prasad; Upadayay, Lokesh (Indian Journal of Pharmacy Practice)
This study was revealed with prescribing patterns of antipsychotic and monitoring practices of psychiatrists in Pune region. We were surveyed 100 psychiatrists in Pune region out of that 50 gave a positive response. This survey includes the study of antipsychotic types prescribed its frequency, the age of the patients and the diagnosis of patients for whom they prescribed these medications. We were prepared a questionnaires format and were distributed to various psychiatrists in the form of hard copy within the Pune region. Questionnaires formats were collected after fulfillment by psychiatrics in the form of hard copy. In that 88 % of psychiatrics prescribed ATAs, most commonly (67 %). Patients diagnosis was include psychotic, mood, anxiety, externalizing, and pervasive developmental disorders. Symptoms persist in patients were aggression, low frustration tolerance, and affect dysregulation was also common. Percent of all prescriptions were for years. Most clinicians monitored patients, but there were wide variations in the type and frequency of tests performed. Our study reveals that there exists considerable variation in patterns of prescribing psychotropic medications and a significant increase in the number of patients suffering from psychiatric illnesses seeking treatment. Prescribing patterns vary due to differences in diagnosis, the discomfort that some psychiatrists feel toward prescribing, differing levels of awareness and recognition due to cultural variances, the perceived negative stigma of mental illness, and insufficient education regarding the etiology and management of psychiatric disorders.
Keywords: Anti-psychotic drugs; prescribing pattern; mental illness